IMPLEMENTATION OF COMBINATION METHOD ON PASSWORD FOR USER ACCESS IN BANK OPERATIONAL ENVIRONMENT - R Fitria Rachmawati (Information Technology Studies Journal (ITECH), 2025)
The development of information and communication technology has now progressed so rapidly and become an inseparable part of human life. The use of this technology has driven rapid business growth, because various information can be easily obtained and presented sophisticatedly, such as compiling electronic documents, performing calculations, sending and reading e-mails, searching for all kinds of information on the internet, and chatting are daily activities that utilize information and communication technology. These positive impacts do not always last well, on the other hand, other parties have thoughts that with bad intentions seek profit by breaking the law. This study explains the scope of information system ethics in terms of the use of passwords as a support for privacy security for system users in the bank's operational environment. The theory used in this study covers the scope of information system ethics, theories related to passwords used in the bank's operational environment. The results of this study are expected to provide deeper knowledge to the general public, and especially in the bank's operational environment, about the importance of information system ethics in terms of implementing combination methods on passwords for user access in the bank's operational environment.